Evaluation Of Antibacterial Activity And Standardization Of Flower Of Myrtus Communis L. - JUVERIA MAHMOOD; M.A.WAHEED; SHAIKH MAHMOOD (International Journal of Pharma and Bio Sciences, 2015)
The present study attempts to investigate in vitro antibacterial activity against bacterial strains and the main aspects included in the study are Phytochemical, physico-chemical studies, organoleptic characters, fluorescence analysis of dried flowers extracts, HPTLC, TLC profile, Heavy metal analysis and Aflatoxin estimation of the dried flowers of M. communis. The antibacterial activity of M. communis flowers was assessed against most prevalent microbes like Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumonia, Escherichia coli, Salmonella typhi against five different extracts by using agar well diffusion method and the Phytochemical, physico-chemical studies, organoleptic characters, fluorescence analysis of dried flowers extracts, HPTLC, TLC profile, Heavy metal analysis and Aflatoxin estimation were analyzed as per the methods described in WHO guidelines. The evaluation of antibacterial activity on chloroform extract was found to be more active than other extracts and among the tested organism Escherichia coli was found to be most sensitive organism followed by Salmonella typhi, Bacillus subtilis, Staphylococcus aureus and Klebsiella pneumonia. When compared with streptomycin (10 mcg) as standard antibiotic. The flowers of M. communis might represents a new antimicrobial source with stable, biologically active components that can establish a scientific base for the use for developing medicine. Further it was standardized according to the methods described in WHO guidelines with respect to Phytochemical, physico-chemical studies, organoleptic characters, fluorescence analysis on flowers extracts were carried out along with HPTLC, TLC profile, Heavy metal analysis and Aflatoxin contamination.